Stay in line - Slater, Teddy (New York : Scholastic, 1996)
Twelve children on a class trip to the zoo have fun grouping themeselves into line of different sizes.
Keywords: Zoo -- Fiction; School field trips -- fiction; Arithmetic -- fiction